2020
DOI: 10.3390/ijerph17176377
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposures Associated with Life Expectancy without and with Disability

Abstract: Policies to extend working lives often do not take into account potentially important health inequalities arising from differences in occupational exposures. Little is known about which occupational exposures are associated with these inequalities. This study aims to examine differences in life expectancy without and with disability by occupational exposures. Longitudinal data (1992–2016) on disability and physical and psychosocial work demands and resources of 2513 (former) workers aged ≥55 years participatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Considering the mean life expectancy at age 55 is larger than at age 65, this difference is comparable to the one we found at age 65. Our earlier study on work conditions and life expectancy at age 55 showed a maximum difference between unfavorable and favorable work conditions of 2.6 years for men and 2.3 for women ( de Wind et al, 2020 ). The latter are smaller than the domain differences found in the current study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Considering the mean life expectancy at age 55 is larger than at age 65, this difference is comparable to the one we found at age 65. Our earlier study on work conditions and life expectancy at age 55 showed a maximum difference between unfavorable and favorable work conditions of 2.6 years for men and 2.3 for women ( de Wind et al, 2020 ). The latter are smaller than the domain differences found in the current study.…”
Section: Discussionmentioning
confidence: 93%
“…Also physical demands have been shown to be associated with increased risk of mortality ( Mikkola et al, 2019 ). In a recent study from our own group, people at age 55 who had physically strenuous jobs regarding repetitive movements and use of force had a 1.5–2.0 years shorter life expectancy than their counterparts with less strenuous jobs, and people who had jobs with a low variation in activities and low autonomy had a 1.1–2.5 years shorter life expectancy than their counterparts with jobs with high variation and autonomy ( de Wind et al, 2020 ). Working conditions may be concentrated in specific occupations, but essentially cut across occupations.…”
Section: Introductionmentioning
confidence: 99%
“…55,[57][58][59] Research from the Longitudinal Aging Study Amsterdam suggested different life expectancy by different occupation and occupational exposures. 60,61 These studies revealed a need to provide specific support regarding the working environment, and the pension policy should be tailored according to individuals' risk of longevity. However, the WPA in our study does not correspond to occupation or occupational exposure in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, motivation, financial status, and physical health were important effect modifiers 55,57–59 . Research from the Longitudinal Aging Study Amsterdam suggested different life expectancy by different occupation and occupational exposures 60,61 . These studies revealed a need to provide specific support regarding the working environment, and the pension policy should be tailored according to individuals' risk of longevity.…”
Section: Discussionmentioning
confidence: 99%
“…The sole consequence of hazardous work that is not addressed by any branch of the social insurance system is the reduction of life expectancy. There are some studies linking worker’s occupation to mortality (Johnson, Sorlie and Backlund, 1999; Katikireddi et al, 2017; Lee et al, 2016) or life expectancy (Moore and Hayward, 1990; de Wind et al, 2020; Deeg, Tavernier and de Breij, 2021). The estimates provided by these range from a maximum difference between favourable and unfavourable working conditions of around 2.5 years (de Wind et al, 2020) to 4.5 years at age 55 (Moore and Hayward, 1990), and around 3.3 years at age 65 (Deeg, Tavernier and de Breij, 2021).…”
Section: Potential Functions Of Special Pension Schemesmentioning
confidence: 99%